Ecological and social values of the community forest managed for rural livelihoods in Sa Kaeo Province, Eastern Thailand - PRAPATSORN YODSA-NGA; JIRATTAYAKORN TEERATINAN; SUPATTHRA PANGKLOM; PANYA WAIBOONYA; BOONTIDA MOUNGSRIMUANGDEE (Society for Indonesian Biodiversity, 2026)
Abstract. Yodsa-Nga P, Teeratinan J, Pangklom S, Waiboonya P, Moungsrimuangdee B. 2026. Ecological and social values of the community forest managed for rural livelihoods in Sa Kaeo Province, Eastern Thailand. Biodiversitas 27 (3): d270341. https://doi.org/10.13057/biodiv/d270341. Community forests are essential in Thailand for supporting local livelihoods and conserving the environment. This research investigates the ecological and social values of the Ban Nong Ma-U Community Forest in Sa Kaeo Province, Eastern Thailand. Ecological characteristics of woody species were assessed in 54 systematically established sampling plots, each measuring 20 × 20 m. Species composition and diversity were evaluated using the importance value index (IVI) and the Shannon-Wiener index (H¢). Biomass of woody species was calculated using allometric equations, and carbon stocks were estimated accordingly. Social values were determined through ethnobotanical indices derived from interviews with 94 residents of Nong Ma-U Village regarding the use of non-timber forest products (NTFPs). In total, 68 species were identified in the sample plots, representing 54 genera and 30 families. Fabaceae was the dominant family, comprising 11 species. Dipterocarpus tuberculatus was the most prevalent tree species, while Suregada multiflora and Sindora siamensis ranked highest among sapling and seedling species based on IVI. The H¢ ranged from 2.48 to 2.96 across tree, sapling, and seedling stages. Tree and sapling biomass were 59.49 and 0.75 ton ha-1, respectively, while carbon stocks for trees and saplings were 27.96 and 0.35 ton C ha-1. A total of 97 NTFPs were recorded, primarily wild plants used for human consumption. Curcuma parviflora, Amorphophallus macrophyllum, Cratoxylum formosum, Azadirachta indica, Amorphophallus paeoniifolius, Curcuma alismatifolia, and Phoenix loureiroi were identified as the most culturally significant NTFP species based on high values of the cultural importance index (CI) and relative importance index (RI). The results indicate that the Ban Nong Ma-U Community Forest provides significant ecological and social benefits to local communities. These benefits include meeting local needs, reliance on NTFPs, carbon sequestration, and the maintenance of local traditions. The implementation of a comprehensive conservation and utilization framework is expected to sustain the resources of Ban Nong Ma-U Community Forest and enhance local livelihoods.